Index based livestock insurance in Ethiopia - CGIAR Research Program on Livestock (2017)
Outputs include: insurance contract design with demonstrated functionality; consortium of partners ready to take IBLI to scale; suite of customised tools; curriculum for the national Meteorological Agency to assess drought to trigger insurance payouts. ILRI is now working on a concept note to guide uptake by the Ethiopian government.